Perception Of Value, Trust In Loyalty Through User Satisfaction Of Pln Mobile Services - Larisma RL Sitanggang; Mesra b; Elfitra Desy Surya (Yayasan Multidimensi Kreatif, 2024)
This study aims to test and analyze Value Perception (X1), Trust (X2), and Customer Loyalty (Y) mediated by Satisfaction (Z). The population in this study is consumers with 80 samples taken. The research was conducted from April to June 2024. This study uses quantitative data processed using the SEM-PLS analysis model with Smart PLS 3.0. application. The data source uses primary data taken directly from respondents and secondary data obtained from interviews with customers who come to PLN UP3 North Medan. The results of the study show that value perception has a positive and significant influence on satisfaction. Trust has a positive and insignificant effect on satisfaction, the satisfaction has a positive and in significant effect on customer loyalty. Value perception, Trust has positive and significant to customer loyalty through satisfaction.